The Design of an Android-based Financial Recording and Investment Simulation Information System - Saputra, Gede Rizky Chandra; Sukarsa, I Made; Andreyana, Putu Veda; Wira Buana, Putu; Wisswani, Ni Wayan (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 12 No 3 (2024): Vol. 12, No. 3, December 2024DO - 10.24843/JIM.2024.v12.i03.p03, 2024)
Financial management and investment have become increasingly important in digital era, where many individuals and organizations face challenges in effectively recording and managing their finances. Address this issue, mobile application has been developed, offering features such as financial recording, investment simulation, loan simulation, and portfolio tracking. The application is designed with user-friendly interface, tailored to meet users' needs for more efficient financial management. Built using Flutter for Android platform and Laravel for backend, application adopts waterfall development method to ensure systematic progress at every stage and employs microservice architecture to support scalability. Testing was conducted using Black Box Testing method to verify application functionality and Post-Study Usability Questionnaire (PSSUQ) involving 30 users to evaluate satisfaction levels. Results show application performs well on its key features, achieving an average PSSUQ score of 1.9, which is better than satisfaction threshold of 2.57, indicating a high level of user satisfaction with this application.